Different Strategies for Accelerated CO2 Absorption in Packed Columns by Application of the Biocatalyst Carbonic Anhydrase. (July 2017) - Leimbrink, Mathias; Limberg, Timo; Kunze, Anna-Katharina; Skiborowski, Mirko
Abstract: Within this work, the combination of an energetically favorable aqueous N-Methyldiethanolamine (MDEA) solution and the enzyme carbonic anhydrase is investigated in a packed column pilot plant. The use of aqueous MDEA solution for CO2 separation is already known from natural gas applications, for which an increased driving force due to the higher partial pressures of CO2 overcompensates reaction kinetic limitations. The objective of the addition of carbonic anhydrase is to countervail the loss of separation efficiency caused by the lower driving force in CO2 capture from power plant flue gases. Hence, carbonic anhydrase acts as a key to harness the energetic advantage of these solvent systems. However, application of the enzyme also poses restrictions on the process. Especially compliance with the enzyme stability limits is challenging for desorption, which is generally performed at high temperatures. In order to determine an optimal implementation of the enzyme into the process the current work presents different strategies how to apply CA as a biocatalyst in reactive absorption processes and shows how absorption efficiency is influenced. For introducing the enzyme to a packed column two approaches are investigated in this study. The simplest way of application is to dissolve the enzyme in the solvent. This allows the enzyme to work exactly where the reaction kinetic limitation can be found, in the liquid boundary layer. However, due to the temperature sensitivity of the enzyme an additional enzyme recovery step prior to the desorber might be necessary if desorption is to be performed at high temperatures. The immobilization of the enzyme inside the absorption column presents an alternative to prevent this additional separation, but may cause additional mass transfer limitations at the solid particles in which the enzyme is immobilized. The immobilization and the necessity of a suitable packing in which the enzyme particles can be filled, also makes this strategy more complicated but allows placing the enzyme at a location of most suitable process conditions in the column. But most importantly it completely avoids that the enzymes experience high temperature in the desorber. Systematic investigations of the influence of specific liquid load, liquid inlet temperature, MDEA-concentration and enzyme immobilization on absorption performance are conducted. Dissolved enzyme showed a nearly three times higher absorption performance than the immobilized enzyme under equivalent operating conditions, however the immobilized enzyme concentration used was effectively 50 times lower, meaning the result is actually quite promising for immobilized CA. From the investigated operating conditions, a liquid inlet temperature of 20 °C, a MDEA concentration of 30 wt.-% and a liquid flow rate of 24 m 3 m -2 h -1 showed the best absorption performance with the dissolved enzyme. The measured absorption rate was 7.57 times higher than without enzyme added.